-
Notifications
You must be signed in to change notification settings - Fork 19
/
Copy pathweib.tex
82 lines (73 loc) · 2.65 KB
/
weib.tex
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
\documentclass[12pt]{article}
\usepackage{a4full}
\begin{document}
\section*{Simple Weibull-Gompertz}
\begin{eqnarray}
\dot{p}_C &=& [E_m] e L^3 (\dot{v}/ L - \dot{r})
\\
\dot{r} &=&\frac{\dot{v} e/ L - (1 + L_T/ L) \dot{k}_M g} {e + g}
\\
\dot{h} &=& \dot{h}_a m_D/ m_D^{\mbox{\tiny ref}}
\\
\frac{d} {dt} m_Q &=& \eta_{QC} \dot{p}_C/ M_V - \dot{r} m_Q
\\
\frac{d} {dt} m_D &=&
m_Q y_{DQ} \dot{k}_W + m_D \dot{k}_G - \dot{r} m_D
\\
\frac{d} {dt} \dot{h} &=& \ddot{q} -
\dot{h} (\dot{r} - \dot{k}_G); \quad
\ddot{q} = m_Q y_{DQ} \dot{k}_W \dot{h}_a/ m_D^{\mbox{\tiny ref}}
\\
\frac{d} {dt} \ddot{q} &=& \ddot{h}_a e (\dot{v}/ L - \dot{r})
- \dot{r} \ddot{q}; \quad
\ddot{h}_a = \dot{h}_a \dot{k}_W y_{DQ} \frac{\eta_{QC}} {m_D^{\mbox{\tiny ref}}}
\frac{[E_m]} {[M_V]}
\end{eqnarray}
\section*{Modified Weibull-Gompertz: $M_D$ acceleration $\propto \dot{p}_C$}
\begin{eqnarray}
\frac{d} {dt} m_Q &=& \eta_{QC} \dot{p}_C/ M_V - \dot{r} m_Q
\\
\frac{d} {dt} m_D &=&
m_Q y_{DQ} \dot{k}_W +
m_D \frac{s_G \dot{p}_C} {[E_m] L_m^3} - \dot{r} m_D
\\
\frac{d} {dt} \dot{h} &=& \ddot{q} - \dot{h} (\dot{r} -
s_G \frac{L^3} {L_m^3} e (\dot{v}/ L - \dot{r}))
\\
\frac{d} {dt} \ddot{q} &=& \ddot{h}_a e (\dot{v}/ L - \dot{r})
- \dot{r} \ddot{q}
\end{eqnarray}
\section*{Modified Weibull-Gompertz: $M_Q$ acceleration $\propto \dot{p}_C$}
\begin{eqnarray}
\frac{d} {dt} m_Q &=& \eta_{QC} \dot{p}_C/ M_V +
m_Q \frac{s_G \dot{p}_C} {[E_m] L_m^3} - \dot{r} m_Q
\\
\frac{d} {dt} m_D &=& m_Q y_{DQ} \dot{k}_W - \dot{r} m_D
\\
\frac{d} {dt} \dot{h} &=& \ddot{q} - \dot{r} \dot{h}; \quad
\ddot{q} = m_Q y_{DQ} \dot{k}_W \dot{h}_a/ m_D^{\mbox{\tiny ref}}
\\
\frac{d} {dt} \ddot{q} &=& (\ddot{q} \frac{L^3} {L_m^3} s_G + \ddot{h}_a)
e (\dot{v}/ L - \dot{r}) - \dot{r} \ddot{q}
\end{eqnarray}
For short growth periods, $\dot{r} = 0$, and constant food, $e = f$
\begin{eqnarray}
\ddot{q}(t) &=& \ddot{a} (\exp(\dot{b} t) - 1); \quad
\ddot{a} = \frac{\ddot{h}_a L_m^3} {s_G (e L_m - L_T)^3}; \quad
\dot{b} = s_G e \dot{v} \frac{(e L_m - L_T)^2} {L_m^3}
\\
\dot{h}(t) &=& \ddot{a} ( \frac{\exp(\dot{b} t) - 1} {\dot{b}} - t)
\\
S(t) &=& \exp \left( - \frac{\ddot{a}} {\dot{b}} \left(
\frac{\exp(\dot{b} t) - 1} {\dot{b}} - t - \dot{b} t^2/ 2
\right) \right)
\end{eqnarray}
for $\dot{h}_G = s_G \dot{v} e (e L_m - L_T)^2 L_m^{-3}$
\begin{equation}\label{eqn:qhS_gomp}
\ddot{q}(t) =
\ddot{q}(0) \exp(t \dot{h}_G); \quad
\dot{h}(t) = \ddot{q}(0) \frac{\exp(t \dot{h}_G) - 1} {\dot{h}_G}; \quad
\Pr \{\underline{a}_{\dagger} > t \} =
\exp(\frac{\ddot{q}(0)} {\dot{h}_G^2} (\exp(t \dot{h}_G) - 1 - t \dot{h}_G))
\end{equation}
\end{document}